’Multilingualising’ Language Education: A Teacher Training Programme for English as a ’Bridge Language’ in Early Childhood Education - Gkaintartzi, Anastasia; Kostoulas, Achilleas; Vitsou, Magda (Journal of Education and Training, 2024)
This article outlines a teacher training programme called: "English in the Kindergarten: Towards Multilingual Education", which was designed and implemented as a response to the introduction of English in Greek state preschools from 2021 onward. The programme aims to develop teachers’ knowledge, skills, and attitudes for the introduction of the English language as a cross-linguistic and cross-cultural bridge and ultimately to promote multilingualism and inclusion in the class. It is theoretically grounded on a critical sociolinguistic approach toward languages in education, which valourises the children’s entire linguistic repertoire and challenges ’parallel monolingualisms’ that typify some initiatives in the field of early (foreign) language education. Classes are reimagined as spaces where learners and teachers engage with age-appropriate experiential and plurilingual practices, art-based learning, drama techniques, and puppetry. At the same time, pluralistic approaches and translanguaging are proposed to be used to leverage children’s linguistic and cultural capitals as they engage with English in early language education, thus enhancing multilingual and intercultural awareness. After discussing the theoretical tenets of the program’s design, an overview of its structure and sample activities is provided as well as extracts from participant teachers’ output and data from its evaluation. The paper concludes with the implications of the programme and the perspective it advances.